The Packing Measure Of Self-Affine Carpets - Peres, Yuval (Mathematical Proceedings of the Cambridge Philosophical Society, 1994)
We show that the seif-affine sets considered by McMullen [15] and Bedford [2] have infinite packing measure in their packing dimension θ except when all non-empty rows of the initial pattern have the same number of rectangles. More precisely, the packing measure is infinite in the gauge tθ|logt|−1 and zero in the gauge tθ|logt|−1−δ for any δ > 0.